Glances of conflict - García Lozano, Francisco José (Razón y fe, 2018)
The cinema, living witness of our lives, could not fail to be present in the Basque conflict. Numerous films and documentaries have recorded the myth, militancy, suffering and complexity of the future of ETA. Although there is no cinematographic masterpiece, nor do the victims or their families have the place they deserve, the courage and civic will of directors and producers have contributed to presenting the complex history of Spain and the Basque Country.